The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1126/science.1323141
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Insulin-Like Growth Factor II Gene by the Wilms Tumor Suppressor WT1

Abstract: The Wilms tumor suppressor gene wt1 encodes a zinc finger DNA binding protein, WT1, that functions as a transcriptional repressor. The fetal mitogen insulin-like growth factor II (IGF-II) is overexpressed in Wilms tumors and may have autocrine effects in tumor progression. The major fetal IGF-II promoter was defined in transient transfection assays as a region spanning from nucleotides -295 to +135, relative to the transcription start site. WT1 bound to multiple sites in this region and functioned as a potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
253
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(265 citation statements)
references
References 26 publications
10
253
1
1
Order By: Relevance
“…Reported target genes for the WT1 protein include both genes involved in growth regulation and genes necessary for induction of di erentiation, such as c-myc, bcl-2 (Hewitt et al, 1995), colony-stimulating factor-1 (CSF-1) (Harrington et al, 1993), transforming growth factor-b1 (TGF-b1) (Dey et al, 1994), insulin-like growth factor 1 receptor (IGF1R) (Werner et al, 1993), insulin-like growth factor II (IGF II) (Drummond et al, 1992), platelet-derived growth factor A-chain (PDGF-A) (Gashler et al, 1992) and retinoic acid receptor-a (RAR-a) (Goodyer et al, 1995). The WT1 protein has been shown to mediate either transcriptional repression or activation, depending on the architecture of the promoter under study and the cell lines in which the transfection assay were performed (Madden et al, , 1993Drummond et al, 1992;Maheswaran et al, 1993;Werner et al, 1993;Wang et al, 1993b).…”
Section: Introductionmentioning
confidence: 99%
“…Reported target genes for the WT1 protein include both genes involved in growth regulation and genes necessary for induction of di erentiation, such as c-myc, bcl-2 (Hewitt et al, 1995), colony-stimulating factor-1 (CSF-1) (Harrington et al, 1993), transforming growth factor-b1 (TGF-b1) (Dey et al, 1994), insulin-like growth factor 1 receptor (IGF1R) (Werner et al, 1993), insulin-like growth factor II (IGF II) (Drummond et al, 1992), platelet-derived growth factor A-chain (PDGF-A) (Gashler et al, 1992) and retinoic acid receptor-a (RAR-a) (Goodyer et al, 1995). The WT1 protein has been shown to mediate either transcriptional repression or activation, depending on the architecture of the promoter under study and the cell lines in which the transfection assay were performed (Madden et al, , 1993Drummond et al, 1992;Maheswaran et al, 1993;Werner et al, 1993;Wang et al, 1993b).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Twothirds of Wilms' tumors maintaining heterozygosity at the IGF2 locus show relaxation of imprinting (Rainier et al, 1993;Ogawa et al, 1993a), allowing expression of both copies, and this is also seen constitutionally in the Beckwith-Wiedemann syndrome (Weksberg et al, 1993). (3) The WT1 gene, whose inactivation accounts for some Wilms' tumors, encodes a zinc-®nger protein that, in vitro, represses expression of IGF-II (Drummond et al, 1992) and of its mitogenic receptor (Werner et al, 1993). The diversity of the molecular abnormalities that can cause increased IGF2 dosage in Wilms' tumor makes it unlikely that it is a mere embryonal marker.…”
Section: Introductionmentioning
confidence: 99%
“…Several G\C box-binding transcription factors have been identified that are involved in P3 regulation via this proximal region. The product of the Wilms' tumour suppressor gene, WT1, is able to repress P3 by binding to different sites in the promoter and within exon 5 [10]. Another factor that binds the same site as WT1, EGR-1, is able to stimulate P3 [11].…”
Section: Introductionmentioning
confidence: 99%